IMPLEMENTING TOTAL PRODUCTIVE MAINTENANCE (TPM) IN MALAYSIAN MANUFACTURING ORGANISATION: AN OPERATIONAL STRATEGY STUDY - Seng, One Yoon; Jantan, Muhamad; Ramayah, T (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2005)
Total Productive Maintenance (TPM) has been recognized as one of the significant operation strategy to regain the production losses due to equipment inefficiency. Many organizations have implemented TPM to improve their equipment efficiency and to obtain the competitive advantage in the global market in terms of cost and quality. In the implementation of TPM in a manufacturing organization, both Human-oriented and Process-oriented Strategy has been identified as critical success factors. This paper, therefore, focuses on the two TPM operational strategies, which is posited, will improve the extent of TPM implementation in manufacturing organizations. This study is an attempt to look at the TPM implementation from the perspective of a developing country such as MalaysiaKeywords: total productive maintenance, strategy, manufacturing, Malaysia